Continuous aperture dose calculation and optimization for volumetric modulated arc therapy. (26th October 2018) - Christiansen, Eric; Heath, Emily; Xu, Tong
Abstract: Although VMAT delivery features continuous gantry rotation and leaf motion, dose calculation is often performed under the dual assumption of discrete apertures changing instantaneously from one discrete angle to the next. In this work, the validity of these two approximations is determined, as well as their impact on the quality of optimized plans. Further, an accurate method of fluence calculation is derived which does not use the discrete aperture approximation, but instead calculates the fluence as the multi-leaf collimator leaves sweep from one position to another. This continuous aperture fluence calculation is integrated in the VMAT optimization process using the open-source treatment planning system matRad. The three-step approach of VMAT optimization is used: fluence map optimization followed by leaf sequencing and direct aperture optimization, with variable leaf speed, gantry rotation speed, and MU rate. The benefit of the continuous aperture VMAT method over the discrete aperture method is determined by comparing the plan quality of discrete aperture and continuous aperture optimized plans, when the former is recalculated using the continuous aperture fluence calculation. Discrete aperture VMAT plans calculated at 4° spacing result in significant dose errors (10%–35%, depending on the anatomical site) as compared to the reference dose (continuous aperture fluence calculation at 0.5° spacing). These errors are greatly reduced (to 0.8%–2%) when the continuous aperture fluence calculation method was used at the same 4° spacing, implying that the dose error is primarily due to the discrete aperture approximation. Whereas all dose objectives were met by the discrete aperture VMAT optimized plan, many of them failed when the dose was recalculated with the continuous aperture fluence calculation. All objectives were met once again when the plan was optimized with the new continuous aperture VMAT optimization. Further, using only half of the beam angles, the continuous aperture VMAT optimization can achieve the same degree of accuracy with only 40% of the computing time as compared with the standard discrete aperture VMAT.